2014
DOI: 10.1371/journal.pone.0085881
|View full text |Cite
|
Sign up to set email alerts
|

Developing Clinical Strength-of-Evidence Approach to Define HIV-Associated Malignancies for Cancer Registration in Kenya

Abstract: BackgroundSub-Saharan Africa cancer registries are beset by an increasing cancer burden further exacerbated by the AIDS epidemic where there are limited capabilities for cancer-AIDS match co-registration. We undertook a pilot study based on a “strength-of-evidence” approach using clinical data that is abstracted at the time of cancer registration for purposes of linking cancer diagnosis to AIDS diagnosis.Methods/FindingsThe standard Nairobi Cancer Registry form was modified for registrars to abstract the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Findings from the pilot study [6] showed that the registry required minimal resources (if any) to collect these additional data hence the registry continued to document HIV as one of its variables.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from the pilot study [6] showed that the registry required minimal resources (if any) to collect these additional data hence the registry continued to document HIV as one of its variables.…”
Section: Methodsmentioning
confidence: 99%
“…38 In addition, concerted efforts to develop and strengthen national cancer registries in sub-Saharan countries have arisen, particularly pertaining to HIV and acquired immunodeficiency syndrome-related cancers. 39 Following a proper diagnosis of BL, every child should also undergo staging of the tumor in order to accurately assess the extent of disease. In resource-rich settings, disease extent informs treatment decisions such that more advanced tumors are treated more aggressively and less advanced tumors require less intensive treatment.…”
Section: Diagnosismentioning
confidence: 99%